What can we learn from long-term creep trends in open pit slopes? - Lupo, J (SSIM 2021: Second International Slope Stability in Mining, 2021)
Slope creep is the time-dependent movement of a slope under gravity loading. In hard rock mines, slope creep is generally characterised as being a short-term episode that precedes slope failure with limited deformation. Long-term slope creep poses a special challenge in assessing open pit slope stability, as the creep rates and magnitudes can make it difficult to interpret and predict slope failure. In addition, the transition from creep to ‘instability’ is unique for each set of circumstances, and this can complicate the application of displacementbased response plans (e.g. suspension of mining, pit evacuation, etc.). Well-established factors that affect slope stability also influence creep, but the behaviour of creeping slopes is not well understood as it falls out of the range of traditional pit slope analyses. This paper presents the results of analyses conducted on long-term slope creep records, ranging from one to several years. The results presented indicate that signatures of potential slope failure may be present well before the slope failure occurs. Correlations between creep rate and total displacement (three-dimensional) appear to provide reasonable guidance to predicting future slope failure, which can then be used to inform mine design (e.g. haul ramp placement, etc.).
Keywords: slope creep